Amyloid-β and α-synuclein cerebrospinal fluid biomarkers and cognition in early Parkinson's disease. Issue 7 (July 2015) - Stav, Ane Løvli; Aarsland, Dag; Johansen, Krisztina Kunszt; Hessen, Erik; Auning, Eirik; Fladby, Tormod
Abstract Introduction Cognitive impairment in early Parkinson's disease (PD) is common and distinct from early Alzheimer's disease. Predictors and mechanisms are only partially known, but α-synuclein, amyloid-β and tau dysmetabolism may be involved. Our aim was to study associations between cerebrospinal fluid biomarkers (CSF) and cognition in non-dementia PD compared to normal controls (NC) and non-PD patients with mild cognitive impairment (MCI non-PD). Methods Patients were classified as having normal, subjective or mild cognitive impairment after cognitive screening. CSF levels of total α-synuclein (t-α-syn), amyloid-β (Aβ) 38, 40 and 42, total tau (T-tau) and phosphorylated tau (P-tau) were measured in 34 NC, 31 early, non-dementia PD and 28 MCI non-PD patients. A well validated neuropsychological test battery was administered. Results In the PD group, 13 had normal cognition, 4 had subjective and 14 mild cognitive impairment. PD patients had significantly lower CSF biomarker levels of t-α-syn, Aβ38, 40 and 42, T-tau and P-tau compared to NC. Compared to MCI non-PD, t-α-syn, Aβ38 and 40, T-tau and P-tau were also lower, while Aβ42 was significantly higher in the PD group. Aβ38 and 40 correlated strongly with t-α-syn levels in PD. Lower Aβ42 was associated with decreased verbal learning, delayed verbal recall and response inhibition in PD. Conclusion While Aβ38, 40 and t-α-syn levels are strongly correlated, only lower Aβ42 was associated with reduced cognitive functions in early PD, mainly connected to medial temporal lobe-based cognitive functions.